A non-rewarding, non-aversive buprenorphine/naltrexone combination attenuates drug-primed reinstatement to cocaine and morphine in rats in a conditioned place preference paradigm - Cordery, Sarah F; Taverner, Alistair; Ridzwan, Irna Elina; Guy, Richard H; Delgado-Charro, M Begoña; Husbands, Stephen M; Bailey, Christopher P (Wiley, 2014)
Concurrent use of cocaine and heroin is a major public health issue with no effective relapse prevention treatment currently available. To this purpose, a combination of buprenorphine and naltrexone, a mixed very-low efficacy mu-opioid receptor agonist/kappa-opioid receptor antagonist/nociceptin receptor agonist, was investigated. The tail-withdrawal and the conditioned place preference (CPP) assays in adult Sprague Dawley rats were used to show that naltrexone dose-dependently blocked the mu-opioid receptor agonism of buprenorphine. Furthermore, in the CPP assay, a combination of 0.3 mg/kg buprenorphine and 3.0 mg/kg naltrexone was aversive. A combination of 0.3 mg/kg buprenorphine and 1.0 mg/kg naltrexone was neither rewarding nor aversive, but still possessed mu-opioid receptor antagonist properties. In the CPP extinction and reinstatement method, a combination of 0.3 mg/kg buprenorphine and 1.0 mg/kg naltrexone completely blocked drug-primed reinstatement in cocaine-conditioned rats (conditioned with 3 mg/kg cocaine, drug prime was 3 mg/kg cocaine) and attenuated drug-primed reinstatement in morphine-conditioned rats (conditioned with 5 mg/kg morphine, drug prime was 1.25 mg/kg morphine). These data add to the growing evidence that a buprenorphine/naltrexone combination may be protective against relapse in a polydrug abuse situation.